GM1 ganglioside enhances the rewarding properties of cocaine in rats - Valdomero, Analía (2010)
GM1 pretreatment enhanced the rewarding properties of cocaine as assessed in the conditioned place preference paradigm. This effect was shown by the lower dosage of cocaine necessary to induce conditioning compared with rats receiving cocaine alone, as well as by the fewer number of sessions necessary to induce place preference. GM1 pretreatment did not modify the plasma level of cocaine, but it induced a significant increase in the brain cocaine level compared with animals receiving cocaine alone. In order to evaluate the possibility that GM1 pretreatment may alter the pharmacokinetic parameters of cocaine, the brain and plasma esterase activities, the plasma bound/free cocaine ratio and the brain blood barrier permeability to i.v. Evans Blue administration were assessed. None of these parameters was modified by the GM1 administration. In addition, GM1 (100μM) did not alter the dopamine transporter inhibition induced by cocaine (10-7-10-5M), as determined by the uptake of [3-H]-dopamine in the microsacs of nucleus accumbens. In conclusion, GM1 pretreatment, which did not have any effect per se, increased the rewarding effect of cocaine, a phenomenon correlated with a significant increase in the brain cocaine levels. The different pharmacokinetic parameters evaluated, as well as the inhibitory effect of cocaine on the dopamine transporter, were not modified by GM1, but it modifies the brain cocaine disposition. Thus, the mechanisms by which GM1 enhanced the rewarding effects of cocaine merit further study. © 2009 Elsevier B.V.